Forking hell. (Economist, 2015)
The article focuses on an ideological and technical dispute concerning the digital currency Bitcoin. It states two of the main developers for the Bitcoin released a competing version of the currency's software on August 15, 2015. It mentions that Bitcoin creator Satoshi Nakamoto disappeared from view in 2011 and had limited the block size of Bitcoins to one megabyte. It comments on the interest of some developers to increase block sizes to increase capacity, and resistance to this move.